Financial expert witness communication : a practical guide to reporting and testimony - Preber, Bradley J. (Hoboken, New Jersey : John Wiley & Sons, 2014)
"The book provides practical guidance on financial forensic expert witnessing for reporting and testimony required in litigation from the standpoint of the expert witness. The focus is on accounting, financial forensics, forensic technology and damages experts who expect to be formally designated as an expert witness. Chapters written by nationally recognized experts include litigation and dispute resolution process, roles for the financial expert witness, retention, responsibilities of the expert witness, privilege, ethics, opinions, litigation reporting, testimony, ADR reporting communicating, the internet, and social media and the financial expert witness"--
Chapter 11 Rebutting the Financial Expert Witness ReportThe Financial Expert Rebuttal; Steps for an Effective Rebuttal; Case Study: Exclusion of the Financial Expert Witness; Risks of Having Only Rebuttal Opinions; Coming Up; Notes; Chapter 12 Discovery Using Deposition; What Is a Deposition?; Deposition Objectives; Coming Up; Chapter 13 Financial Expert Witness Deposition Preparation; Preparation for Deposition; Expected Deposition Questions; Confer with Client Legal Counsel; Leading Up to Deposition; Coming Up; Chapter 14 Financial Expert Witness Deposition Testimony; Deposition Testimony
Machine generated contents note: Disclaimer Foreword Preface Acknowledgments Part One: Dispute Resolution and the Financial Expert Chapter 1 Value of the Financial Expert in Litigation and Dispute Resolution Why Be a Financial Expert Witness? Value of the Financial Expert Witness under Federal Rules Enhancing Value Using the Litigation Process Coming Up Notes Chapter 2 Roles Suited for the Financial Expert The "Big 3": Liability, Causation and Damages Financial Expert Assignments Roles for the Financial Expert Matters Suited for the Financial Expert Financial Expert Litigation Services Coming Up Notes Chapter 3 Retention of the Financial Expert Finding Financial Experts Prospective Client Due Diligence Pre-Engagement Communications Selection of the Financial Expert Witness Coming Up Notes Chapter 4 Getting Started As a Financial Expert Getting Started Coming Up Notes Chapter 5 Civil Litigation and Dispute Resolution Processes Civil Litigation Actions and Proceedings Alternate Dispute Resolution Coming Up Notes Part Two: Financial Expert Rules, Case Precedent, and Ethics Chapter 6 Federal Rules of Evidence for the Financial Expert Witness Evidentiary Rules on Expert Witness Opinions and Testimony Scientific, Technical, or Other Specialized Knowledge Coming Up Notes Chapter 7 Federal Rules of Civil Procedure for the Financial Expert Witness Procedural Rules on Expert Witness Reporting and Testimony Coming Up Notes Chapter 8 Basic Litigation Knowledge for the Financial Expert Witness Laws and Rules Legal Precedent Orders Court Rules and Policies Privileged Communications Professional Standards Coming Up Notes Chapter 9 Professional Ethics Considerations Professional Ethics Ethical Considerations for the Financial Expert Witness Trial Coming Up Part Three: Financial Expert Witness Reports and Testimony Chapter 10 Preparing the Financial Expert Witness Report Federal Rules on Financial Expert Witness Disclosure A P.R.A.C.T.I.C.A.L. Way to Prepare a Financial Expert Report Organization of the Financial Expert Witness Written Report Writing the Financial Expert Witness Report Caveats to Consider Exhibits Quality Control for Financial Expert Witness Reports Coming Up Notes Chapter 11 Rebutting the Financial Expert Witness Report The Financial Expert Rebuttal Steps for an Effective Rebuttal Case Study: Exclusion of the Financial Expert Witness Risks of Having Only Rebuttal Opinions Coming Up Notes Chapter 12 Discovery Using Deposition What is a Deposition? Deposition Objectives Coming Up Chapter 13 Financial Expert Witness Deposition Preparation Preparation for Deposition Expected Deposition Questions Confer with Client Legal Counsel Leading Up to Deposition Coming Up Chapter 14 Financial Expert Witness Deposition Testimony Deposition Testimony Post-Deposition Activities Coming Up Notes Chapter 15 The Financial Expert Witness and Motions and Hearings Motions Hearings Coming Up Notes Chapter 16 Financial Expert Witness Trial Testimony Types of Trials Components of Trial Examination Preparation for Trial Testimony Objections Coming Up Notes Chapter 17 Financial Expert Witness Direct Examination Direct Examination Direct Examination Outline Trial Demonstratives Preemptive Cross-Examination Use of the Expert Report in Trial Redirect Examination Rebuttal Testimony Coming Up Notes Chapter 18 Financial Expert Witness Cross-examination Cross-examination Objectives of Cross-examination Cross-examination Techniques Ten Commandments of Cross-examination Surviving Cross-examination Recross-examination Coming Up Notes Part Four: Alternative Dispute Resolution Chapter 19 Alternative Dispute Resolution: Mediation Mediation Process Financial Expert Participation in Mediation Mediation Activities Coming Up Notes Chapter 20 Alternative Dispute Resolution: Arbitration The Arbitration Process Structure of Arbitration Arbitration Activities Financial Expert Participation in Arbitration Coming Up Notes Chapter 21 Alternative Dispute Resolution: Neutral Accounting Arbitration Neutral Accounting Arbitration Neutral Accounting Arbitration Process In Closing About the Website About the Author Bibliography and Suggested References Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Forensic accounting -- United States; Evidence, Expert -- United States; BUSINESS & ECONOMICS -- Accounting -- General; Evidence, Expert; Forensic accounting; United States; Electronic books; Electronic books